2005
DOI: 10.1007/s10725-005-0861-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Short-term Red Radiation and Choline Compounds on Cytokinin Content, Chlorophyll Accumulation and Photomorphogenesis in Wheat Seedlings

Abstract: Effects of choline compounds (2-chloroethyltrimethylammonium chloride and 2-ethyltrimethylammonium chloride) as well as red radiation (R) pulse on the dynamics of cytokinin changes, growth and chlorophyll (a + b) accumulation were studied during the growth and greening of etiolated wheat seedlings (Triticum aestivum L., var. Mironovskaya-808). The seedlings were grown for 120 h in the dark and then exposed for 72 h to white light. Pre-treatment of caryopses with cholines and pre-irradiation of etiolated seedli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…For example, 2-chloroethyltrimethylammonium chloride and 2-ethyltrimethylammonium chloride increased plant chlorophyll content, which was related to its increase in leaf cytokinin levels. 42 Genetic engineering of the biosynthesis of glycinebetaine could enlarge the fruit size and enhance the productivity of tomato, which was related to the contents of phytohormones, such as auxin, brassinolide, gibberellin, and cytokini. 43 Moreover, JA-GA network influences the intensity of defense responses.…”
Section: Resultsmentioning
confidence: 99%
“…For example, 2-chloroethyltrimethylammonium chloride and 2-ethyltrimethylammonium chloride increased plant chlorophyll content, which was related to its increase in leaf cytokinin levels. 42 Genetic engineering of the biosynthesis of glycinebetaine could enlarge the fruit size and enhance the productivity of tomato, which was related to the contents of phytohormones, such as auxin, brassinolide, gibberellin, and cytokini. 43 Moreover, JA-GA network influences the intensity of defense responses.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, electrophysical treatment methods for plants and seeds of grain, vegetable and legume crops have been introduced extensively into agricultural practices to intensify plant growing [8,9]. Physical factors influencing seeds may include electromagnetic fields of various ranges (from -radiation to UHF radio-frequency range), X-ray radiation, ultraviolet and optical radiation (particularly, laser red radiation with = 632.8 nm), infrared radiation, electric corona field, and ultrasonic exposure [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the capacity to scavenge active oxygen species as well as proline accumulation may be manipulated by using plant growth regulators (Singh andUsha 2003, Diaz et al 2005). Choline chloride (CC) could regulate lipid concentration and composition (Novitskaya et al 2004), affect cytokinin concentration and morphogenesis (Kreslavski et al 2005), and increase resistance of photosynthetic apparatus to UV-B radiation and elevated temperature (Kreslavski et al 2001). Whether CC can increase the tolerance of photosynthetic apparatus to drought stress to our knowledge is not clear.…”
Section: Introductionmentioning
confidence: 99%